An Example of Traditional Houses in Maras: 'Gozluklu Ali House' - Pakoz, Aslihan Ece; Tuncer, Faruk (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
This study aimed to describe the general characteristics of structures of traditional civil architecture in the city center of Kahramanmaras. The study comprised 50 houses, all listed as cultural assets, in the old neighborhoods of Ekmekci, Gazipasa, Kayabasi, Kurtulus, Turan and Yorukselim in the city of Maras. Maps of the traditional urban fabric, old photographs and engravings, and listings information for the structures provided by both the Culture Heritage Protection Regional Council Office in Adana and Kahramanmaras Museum Directorate formed the basis for the research. Examination of all written and visual materials available on these structures and surveys of the structures themselves allowed for the creation of a general picture of traditional civil architecture in the city of Kahramanmaras. The research concluded that a wide range of variables, from climate and topography to the natural environment and economic and social structure, were influential in the formation of traditional Maras houses. The study also documents Gozluklu Ali House, an example of civil architecture in Kahramanmaras which has survived to the present day. The house is evaluated in light of contemporary protection principles, and some recommendations for its preservation are made. This work evaluates some of the structures that constitute the civil architecture of the city of Kahramanmaras, and provides recommendations for their protection and preservation.
Keywords: Traditional house; Gozluklu Ali House; Maras; architecture; restoration